2017
DOI: 10.1111/ele.12767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiple global change drivers on terrestrial carbon storage: additive effects are common

Abstract: The interactive effects of multiple global change drivers on terrestrial carbon (C) storage remain poorly understood. Here, we synthesise data from 633 published studies to show how the interactive effects of multiple drivers are generally additive (i.e. not differing from the sum of their individual effects) rather than synergistic or antagonistic. We further show that (1) elevated CO , warming, N addition, P addition and increased rainfall, all exerted positive individual effects on plant C pools at both sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
155
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 43 publications
(121 reference statements)
24
155
3
1
Order By: Relevance
“…The effect of one environmental change driver or the combined effect of a driver pair was defined as the response of a variable (e.g., soil N concentration) in a treated sample compared with the value of that variable in the corresponding control (Yue, Fornara, Yang, Peng, Peng et al, ), and was described by lnRR (Hedges et al, ). The calculations of lnRR, the associated variance ( ν 1 ) and weight ( w 1 ) of each lnRR, and the weighted mean lnRR (lnRR ++ ) are described in detail in Supporting Information Text S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of one environmental change driver or the combined effect of a driver pair was defined as the response of a variable (e.g., soil N concentration) in a treated sample compared with the value of that variable in the corresponding control (Yue, Fornara, Yang, Peng, Peng et al, ), and was described by lnRR (Hedges et al, ). The calculations of lnRR, the associated variance ( ν 1 ) and weight ( w 1 ) of each lnRR, and the weighted mean lnRR (lnRR ++ ) are described in detail in Supporting Information Text S1.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple environmental change drivers likely act simultaneously and influence a wide range of ecological and biogeochemical processes (Reich et al, ; Yue, Fornara, Yang, Peng, Peng et al, ); thus, the combined effects of multiple drivers on N cycling may be more important than the corresponding individual effects. For instance, a recent meta‐analysis (Li, Niu, & Yu, ) showed how the combined effect of N and P additions on plant N concentration tends to be higher than their individual effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), ultimately promoting terrestrial net primary production (NPP) and soil C storage (Yue et al . ). On the other hand, soil C input enhanced by elevated atmospheric CO 2 may also increase soil CO 2 emissions, stimulating some soil C release back to the atmosphere (van Groenigen et al .…”
Section: Introductionmentioning
confidence: 97%
“…Increased temperature may affect metabolic rates, reduce the abundance of habitat‐forming species, decrease ocean productivity, alter food web dynamics and shift species distributions in marine ecosystems (Hoegh‐Guldberg & Bruno, ), while in terrestrial ecosystems increased temperature has been found to influence carbon (Yue et al, ) and nitrogen (Bai et al, ) storage and increase biomass accumulation in plants (Lin, Xia, & Wan, ). Consequently, the increase in temperature may affect various aspects of the performance of aquatic and terrestrial organisms, including growth, survival, photosynthesis, metabolism (e.g., ethylene evolution, respiration transpiration) and development.…”
Section: Introductionmentioning
confidence: 99%